Significant Role of Third Person in the Distribution to the Number of Divorce Cases in Sidoarjo: Peran Signifikan Pelakor atau Pebinor dalam Sebaran Jumlah Kasus Perceraian di Sidoarjo - Irani, Mercy Cindia Ayu; Mediawati, Noor Fatimah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the influence of actors and directors in the distribution of the number of divorce cases in Sidoarjo Regency. The research method used in this research is socio legal research. The research was conducted by collecting the required data, then leading to the problem identification process which ultimately refers to problem solving. From this study it can be concluded that the adultery factor as a cause of divorce in the Sidoarjo Religious Court has quite a large influence on the high divorce rate, which is in the 5th position based on data from 2017 to 2020. However, when combined with the effects or impacts of the presence of the perpetrator or the partner, which causes the husband and wife to feel uneasy (either in the form of domestic violence, disputes, or one party finally leaves the other), then the influence of the actor or the partner can be the main cause of divorce in Sidoarjo. The next conclusion obtained is that the actions committed by actors and supervisors include acts against the law (civil) as well as violating the law (criminal). It is said to be against the law because it is stated in Article 27 BW. Then the actions of the actors and directors are also said to be unlawful acts, because infidelity acts that lead to adultery are regulated in Articles 284, 417, and 484 of the Criminal Code. The sanctions obtained are also listed in it.